The Kit-Cat Club - Field, Ophelia (Harper Perennial, 2009)
Ophelia Field's 'Kit-Cat Club' is a story of a changing time in 17th-century Britain, during the reigns of Queen Anne and George I, when a group of men and their enterprising initiatives paved the way for new literary and political viewpoints, born out of the most unexpected circumstances.